Lexical meaning: the beginning - Indriyani, Ni Putu (International research journal of management, IT and social sciences, 2015)
The lexical meaning is the meaning of a word is constituted by its contextual relations. Lexical meaning concerned with the relationship between words and meanings. This article uses literary works like songs for analysis. “The Beginning” song from a band called ONE OK ROCK. The researcher chose “OOR” songs because their song is very interesting to examine and research. For me, their song tells us about life. And then, their songs are about life that has the same story with some peoples in the daily fact. This article used a descriptive qualitative approach. The qualitative method was a research procedure which results in descriptive data including written and oral word from the research objectives whether it is from society or books. The researcher took the data from internet social media. The researcher analyzed these lyrics with one word. Lexical and contextual meaning that the researcher analyzed, not all words were analyzed. The researcher found a lot of words can analyze their lexical or denotation and the contextual meaning. The researcher just explains some word to analysis.